SALM5 trans-synaptically interacts with LAR-RPTPs in a splicing-dependent manner to regulate synapse development - Choi, Yeonsoo (Sci Rep, 2016)
Synaptogenic adhesion molecules play critical roles in synapse formation. SALM5/Lrfn5, a SALM/Lrfn family adhesion molecule implicated in autism spectrum disorders (ASDs) and schizophrenia, induces presynaptic differentiation in contacting axons, but its presynaptic ligand remains unknown. We found that SALM5 interacts with the Ig domains of LAR family receptor protein tyrosine phosphatases (LAR-RPTPs; LAR, PTPδ, and PTPσ). These interactions are strongly inhibited by the splice insert B in the Ig domain region of LAR-RPTPs, and mediate SALM5-dependent presynaptic differentiation in contacting axons. In addition, SALM5 regulates AMPA receptor-mediated synaptic transmission through mechanisms involving the interaction of postsynaptic SALM5 with presynaptic LAR-RPTPs. These results suggest that postsynaptic SALM5 promotes synapse development by trans-synaptically interacting with presynaptic LAR-RPTPs and is important for the regulation of excitatory synaptic strength.